2022
DOI: 10.1039/d2cp03319d
|View full text |Cite
|
Sign up to set email alerts
|

The nearly free electron states and the conductivity limited by electron–phonon scattering of an OH-terminated MXene material, a case study of the Hf2C(OH)2 monolayer

Abstract: To reduce the electron-phonon scattering is always desirable for realizing the high conductivity of actual materials at room temperature. It is seemingly feasible in some OH-terminated MXenes such as the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(143 reference statements)
0
1
0
Order By: Relevance
“…MXene has shown excellent catalytic, electronic and magnetic properties, and has a range of practical applications, such as electrocatalysis, [15][16][17] lithium-ion batteries, [18][19][20] electromagnetic shielding 21 and electronic devices. 22,23 In particular, for electrocatalytic hydrogen evolution, the high specific surface area, excellent electronic conductivity and adjustable surface termination of MXene materials make them a promising candidate for low-cost HER catalysts. [24][25][26] However, it is reported that the key catalytic performances of pure MXenes are still far from ideal, in the aspects of both H adsorption energy and the reaction rate.…”
Section: Introductionmentioning
confidence: 99%
“…MXene has shown excellent catalytic, electronic and magnetic properties, and has a range of practical applications, such as electrocatalysis, [15][16][17] lithium-ion batteries, [18][19][20] electromagnetic shielding 21 and electronic devices. 22,23 In particular, for electrocatalytic hydrogen evolution, the high specific surface area, excellent electronic conductivity and adjustable surface termination of MXene materials make them a promising candidate for low-cost HER catalysts. [24][25][26] However, it is reported that the key catalytic performances of pure MXenes are still far from ideal, in the aspects of both H adsorption energy and the reaction rate.…”
Section: Introductionmentioning
confidence: 99%